Discussion of the Predictive Power of First-Quarter Earnings Reports: A Replication - Welsch, Glenn A. (Journal of Accounting Research, 1966)
This paper, based on an empirical research study, is an interesting one in that it not only reports on the usefulness (or perhaps more appropriately the inadequacy) of first-quarter financial reports for investors but also points up three significant issues: that is, 1) why are they issued, 2) why are they not more useful, 3) how they can be made more useful. Prior to briefly elaborating on each of these three points, I would like to say that, in preparing these remarks, I attempted to make them more pragmatic than critical. Several years ago I heard David Green give a speech on this topic and, in my judgment, he made some interesting suggestions and posed some excellent questions; as a consequence, I am pleased to see this additional study on it. Certainly, this study does accent again the problem of external versus internal reporting in a somewhat different dimension. This study, as I understand it, was devoted exclusively to the problem of external reporting via quarterly reports as opposed to internal reporting for internal purposes. In this context I would say that, certainly from the internal reporting point of view, the conclusions would not be appropriate, since I have a very firm conviction that at least the better managements are able to much more accurately project the amount of their potential income for the year-after the first-quarter results are available-than is indicated by any of the interim models and approaches included in the study. As you know, for many years more informed managements have utilized a procedure for internal purposes that has been appropriately called reprojection, whereby from month to month or quarter to quarter there is a reprojection of the incomes, revenues, profits, and related returns for the remainder of the year which is added to the actual results to date.